Electrodeposition of CoNi Bimetallic Catalyst for Ethanol Electrooxidation Application - Abdul Asywalul Fazri; Alvida Nor Puspita; Selvia Ningsih; Annisa Auliya (Pusat Inovasi Sains, 2023)
Platinum is potentially employed as a catalyst in direct ethanol fuel cells (DEFCs). However, its scarcity and susceptibility to carbon monoxide poisoning give rise to novel challenges necessitating resolution. Transition metals such as nickel and cobalt are regarded as highly auspicious catalysts for DEFCs due to their perceived potential to reduce the expenditure associated with the synthesis procedure. In the present investigation, the synthesis of a cobalt-nickel (CoNi) catalyst with bimetallic properties was effectively accomplished through the electrodeposition technique utilizing the stimulator mode. Subsequently, an evaluation was conducted to assess the catalyst's proficiency in ethanol electrooxidation. The CoNi samples underwent comprehensive characterization through the utilization of various analytical techniques, namely X-ray diffraction (XRD), scanning electron microscopy (SEM), elemental dispersive X-ray analysis, and electrochemical impedance spectroscopy (EIS). The XRD analysis confirmed the formation of CoNi, while the SEM characterization demonstrated that the CoNi samples exhibited a homogeneous morphological feature. The impedance measured by the EIS technique displayed a resistance to charge transfer value of 21.21 kΩ, while the solution resistance value amounted to 66.67 kΩ. The catalytic efficiency of the specimens in ethanol electrooxidation was evaluated using the cyclic voltammetry technique, resulting in a peak current density of 3.14 mA/cm2 proving the potential of bimetallic CoNi to be a low-cost catalyst for ethanol electrooxidation process.